2009
DOI: 10.2141/jpsa.46.169
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dietary Methionine in Poultry Production

Abstract: Synthetic DL-methionine (DLM) supplements poultry diets to enhance production. The bioe cacy of liquid methionine is generally lower than that of powder methionine; however, if the level of total sulfur amino acids (TSAA) is set to the commercial recommendation, the bioe cacy of liquid methionine seems to be equal to that of powder methionine (equimolar basis). Absorption and transportation in the segment of the jejunum di er between liquid and powder methionine because multiple systems are involved. Methionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
108
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(113 citation statements)
references
References 106 publications
2
108
0
3
Order By: Relevance
“…Methionine plays an important role in metabolism (Shafer et al, 1998;Bunchasak, 2009). Among the essential amino acids, methionine is the most studied because it is the first limiting amino acid in the formulation of diets based on corn and soybean meal (Barbosa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Methionine plays an important role in metabolism (Shafer et al, 1998;Bunchasak, 2009). Among the essential amino acids, methionine is the most studied because it is the first limiting amino acid in the formulation of diets based on corn and soybean meal (Barbosa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been reported that lean chicks required a higher concentrations of sulfur-containing amino acids than fat-type chicken (Geraert et al, 1987;Leclercq et al, 1993;Alleman et al, 2000), indicating that chicks with different HW may also have different sulfur-containing amino acids requirement, which was partially evidenced in the our previous finding (Chen et al, 2013). Sulfur-containing amino acids as methionine and cysteine play vital role in the antioxidant system (Bunchasak, 2009;Tesseraud et al, 2009). Thus, the compromised antioxidant capacity of light broilers at early age may be due to a higher sulfur-containing amino acids requirement and compromised antioxidants synthesis ability, which would gradually disappeared as the feed intake increased.…”
Section: Resultsmentioning
confidence: 50%
“…However, several researchers reported that there was no difference in bioefficacy between DLM and HMB (Reid et al, 1982;Harms and Russell, 1994;Wideman et al, 1994). In broiler chickens, moreover, we have concluded that as long as TSAA requirement is set at the commercial or maximal requirement, bioefficacy of HMB relative to DLM on a weight basis seems to be 88% Bunchasak, 2009).…”
Section: Introductionmentioning
confidence: 62%
“…Commercial laying hens require higher methionine than NRC (1994) recommendation (Liu et al, 2004a,b;Bunchasak, 2009). According to Cao et al (1992), Schutte et al (1994) and Bunchasak and Silapasorn (2005) the requirements of methionine and TSAA for maximal egg production were around 424 to 440 and 740 to 811 mg/hen/day, respectively.…”
Section: Egg Production Performancementioning
confidence: 99%